Coral restoration for coastal resilience: Integrating ecology, hydrodynamics, and engineering at multiple scales - Viehman, T. Shay; Reguero, Borja G.; Lenihan, Hunter S.; Rosman, Johanna H.; Storlazzi, Curt D.; Goergen, Elizabeth A.; Canals Silander, Miguel F.; Groves, Sarah H.; Holstein, Daniel M.; Bruckner, Andrew W.; Carrick, Jane V.; Haus, Brian K.; et al. (Ecosphere (Washington, D.C), 2023)
The loss of functional and accreting coral reefs reduces coastal protection and resilience for tropical coastlines. Coral restoration has potential for recovering healthy reefs that can mitigate risks from coastal hazards and increase sustainability. However, scaling up restoration to the large extent needed for coastal protection requires integrated application of principles from coastal engineering, hydrodynamics, and ecology across multiple spatial scales, as well as filling missing knowledge gaps across disciplines. This synthesis aims to identify how scientific understanding of multidisciplinary processes at interconnected scales can advance coral reef restoration. The work is placed within the context of a decision support framework to evaluate the design and effectiveness of coral restoration for coastal resilience. Successfully linking multidisciplinary science with restoration practice will ensure that future large‐scale coral reef restorations maximize protection for at‐risk coastal communities.